In-vitro free radical scavenging activity of Ixora coccinea L - Rumana Jahangir; Raushanara Akter; Md. Ashraful Alam; Moni Rani Saha (Bangladesh Pharmacological Society, 2008)
Antioxidant activity of the methanol extract of Ixora coccinea L. was determined by DPPH free radical scavenging assay, reducing power and total antioxidant capacity using phosphomolybdenum method. Preliminary phytochemical screening revealed that the extract of the flower of I. coccinea possesses flavonoids, steroids and tannin materials. The extract showed significant activities in all antioxidant assays compared to the standard antioxidant in a dose dependent manner and remarkable activities to scavenge reactive oxygen species (ROS) may be attributed to the high amount of hydrophilic phenolics. In DPPH radical scavenging assay the IC50 value of the extract was found to be 100.53 μg/mL while ascorbic acid had the IC50 value 58.92 μg/mL. Moreover, I. coccinea extract showed strong reducing power and total antioxidant capacity.